Respuesta :
Answer:
6.2 + (6.2 + 9.4) ⇒ A
6.2 - (-6.2 - 9.4) ⇒ E
Step-by-step explanation:
* Lets revise some definitions to solve the problem
- Associative property states that you can re-group numbers and you
will get the same answer [(a + b) + c = a + (b + c)]
- Additive inverse of a number means reverse the sign of the number
the additive inverse of x is -x
- The expression is (6.2 + 6.2) + 9.4
- We want to find which of the following expressions are equivalent
to this expression
- By using associative property we can write the expression as
6.2 + (6.2 + 9.4)
∴ (6.2 + 6.2) + 9.4 = 6.2 + (6.2 + 9.4)
- Multiply (-) by the additive inverse of number is the number itself
If a number is x and its additive inverse is -x, then (-) × (-x) = x
∵ -6.2 is additive inverse of 6.2
∵ (-)(-6.2) = 6.2
∵ -9.4 is additive inverse of 9.4
∵ (-)(-9.4) = 9.4
∴ 6.2 - (-6.2 - 9.4) = 6.2 + 6.2 + 9.4
∴ (6.2 + 6.2) + 9.4 = 6.2 - (-6.2 - 9.4)
* The answers are A and E
Answer:
6.2 + (6.2 + 9.4) ⇒ A
6.2 - (-6.2 - 9.4) ⇒ E
Step-by-step explanation:
your welcome i hope you pass <3